(untitled) (Indian Journal of Public Health Research & Development, 2021)
The purpose of this study was to investigate the practice and challenges of women executive members in their participations in decision making in the National Sport organizations of Ethiopia. In the study, 21 federations,4 associations and 2 committees were included. We applied descriptive design with qualitative and quantitative method to conduct the study and the participants,from these organizations, were executive officers (n=162), general secretaries (n=27), and experts (n=27). The samples from each of the population unit were selected using universal sampling technique. For analyzing the collected data, Pearson Chisquare(sig) and descriptive statistics including computation of percentile and mean were used. The results reveal that women executive officers in most originations have shown low performance and low participation indecision making and policy implementation of the organizations. The major inhibiting challenges have been found to be incompetence (p<0.002), lack of conducive working conditions (p<0.004)and lack of time to make contribution in the organizations (p<0.006). To increase women’s performance and participation in decision making in the national sport organizations, it is essential to change the work place environment and empower them through recurrent training workshops